Adhering to the seasonal cycles for fishing - Mumbai Archive Project Team (Jio Institute, 2024)
The fishing season in Mumbai is primarily from August to May, with a significant break during the monsoon months of June and July for both safety and sustainability reasons. The Koli fishermen and other fishing communities adhere to these seasonal cycles and regulations to ensure the continued health and productivity of their fishing grounds.